2013
DOI: 10.1002/ange.201302245
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal Magnetic Core–Shell Nanoparticles for Effective Stem‐Cell Differentiation and Imaging

Abstract: Spezialtransport! Das Titelsystem aus einem stark magnetischen Kern und einer dünnen einheitlichen Goldhülle wurde synthetisiert und für den magnetisch erleichterten Transport von genetischem Material (siRNA oder Plasmid‐DNA) in neurale Stammzellen (NSCs) genutzt, um so deren neurale Differenzierung raumzeitlich und biokompatibel zu steuern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 44 publications
(25 reference statements)
0
5
0
Order By: Relevance
“… 37 Then, citrate-capped MCNPs were synthesized according to previously reported methods with slight modifications. 32 The as-synthesized citrate-capped MCNPs were found to have a hydrodynamic diameter of 15.4 nm ( Figure 2 b). Thereafter these MCNPs were coated with branched polyethylenimine (PEI, MW = 10 kDa) via electrostatic interactions to afford an overall positive charge to the complex.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“… 37 Then, citrate-capped MCNPs were synthesized according to previously reported methods with slight modifications. 32 The as-synthesized citrate-capped MCNPs were found to have a hydrodynamic diameter of 15.4 nm ( Figure 2 b). Thereafter these MCNPs were coated with branched polyethylenimine (PEI, MW = 10 kDa) via electrostatic interactions to afford an overall positive charge to the complex.…”
Section: Resultsmentioning
confidence: 98%
“… 29 31 Additionally, our group as well as others have recently demonstrated that these MNPs can be further modified with a gold shell, thus having both magnetic and plasmonic properties that can be utilized for various biological applications including cell targeting, imaging, and chemotherapy. 32 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“… 45 47 Third, the AuNP backbone of NanoScript can be replaced with other types of nanoparticles, such as upconverting nanoparticles and magnetic core–shell nanoparticles, for potential applications such as tracking gene regulation in real time through infrared imaging or magnetic resonance imaging (MRI), respectively. 43 , 48 Finally, the most advantageous feature of NanoScript is its tunable components, by simply redesigning the hairpin polyamide DBD sequence to target regulatory genes such as those involved in differentiation. However, it should be noted that, due to the short DBD targeting sequence, there is a possibility for interactions with off-target genes; hence, further optimization by designing DBDs with longer sequences to target longer DNA sequences would further enhance the NanoScript platform.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Lee and coworkers used a magnetofection-based approach to efficiently delivery MNPs into neural stem cells (NSCs) to induce neuronal differentiation. 38 They used zinc-doped MNPs, ZnFe 2 O 4 , as a core and synthesized a gold shell to develop a magnetic core-shell nanoparticle (MCNP) (Figure 3(a)-(c)). The purpose of the outer gold shell is to increase biocompatibility, enable multiple biomolecules to anchor onto a single nanoparticle, and prevent free radical formation from the MNP core.…”
Section: Magnetically Facilitated Delivery For Enhanced Stem Cell Difmentioning
confidence: 99%